Description of a new species of cave mite, Miracarus grootaerti, and comparison with M. abeloosi, Lions, 1978 (Acari, Oribatida) - Wauthy, Georges; Ducarme, Xavier (Zootaxa, 2011)
Miracarus grootaerti, new species, is described from a cave in South Belgium. It is compared with another species, M. abeloosi. Miracarus grootaerti shows the following unique or very uncommon apomorphic traits: (1) postero-lateral carinae kx on the prodorsum in contact with the pteromorphs; (2) an anterior shift of the sejugal stigmata; and (3) a rutellar microtube.